Drought tolerance and acclimation in Pinus ponderosa seedlings: the influence of nitrogen form. (25th April 2020) - Sigala, José A; Uscola, Mercedes; Oliet, Juan A; Jacobs, Douglass F
Abstract: Drought is a limiting factor to forest regeneration and restoration, which is likely to increase in intensity and duration under future climates. Nitrogen (N) nutrition is related to drought-resistance mechanisms in trees. However, the influence of chemical N form (inorganic and organic N) on physiological traits related to drought resistance has been sparsely studied in conifer seedlings. We investigated the effect of N forms on morpho-physiological traits of Pinus ponderosa Dougl. ex Laws. seedlings and subsequent influences in drought tolerance and acclimation. One-year-old seedlings were fertilized during 10 weeks at 9 mM N with different N forms [either NH4 +, NO3 − or organic N (amino acids mixture)] in their second year of growth. After fertilization, we measured traits associated with intrinsic drought tolerance (shoot water relations, osmotic regulation, photosynthesis and cell membrane stability). Seedlings were then subjected to an 8-week drought period at varying drought intensities to evaluate plant acclimation mechanisms. We demonstrated that P. ponderosa seedlings could efficiently use amino acids as a primary N source, showing similar performance to those grown with inorganic N forms. Nitrogen form influenced mainly drought-acclimation mechanisms rather than intrinsic drought tolerance. Osmotic potential at saturation (Ψπsat ) was marginally affected by N form, and a significant relationship between proline concentration in needles and Ψπsat was found. During acclimation, seedlings fertilized with organic N minimized needle senescence, retained more nutrients in the oldest needles, had maximum increments in proline concentration and hastened the development of water-use efficiency mechanisms compared with those fertilized with inorganic N sources. Our results suggest an improved physiological drought acclimation of organic N-fertilized seedlings.